2020
DOI: 10.1007/s11192-020-03764-3
|View full text |Cite
|
Sign up to set email alerts
|

Number of references: a large-scale study of interval ratios

Abstract: The paper presents a large-scale study (covering 26,998,764 items) of the development in the number of references over time in three document types (articles; reviews; notes) from seven fields (Arts and Humanities; Social Sciences; Computer Science; Mathematics; Engineering; Medicine; Physics and Astronomy). Using interval ratios instead of average numbers, the paper makes it possible to follow the development, and to locate the main causes of growth in the number of references over time. The results show si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Yet, the inflection point was not explicitly specified. For now, we are sure that, for most disciplines, the inflection point did not occur in 2005 [9], nor in 2013 [1], nor in 2015 [10], and not even by 2019 (shown in Fig 2, also in [11]). It appears that the reference lists of journal articles have undergone a runaway process of ever-expanding increase.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Yet, the inflection point was not explicitly specified. For now, we are sure that, for most disciplines, the inflection point did not occur in 2005 [9], nor in 2013 [1], nor in 2015 [10], and not even by 2019 (shown in Fig 2, also in [11]). It appears that the reference lists of journal articles have undergone a runaway process of ever-expanding increase.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, researchers have speculated about other factors, including the advancement of teamwork and multiple authorships [5], pressure from reviewers [2], and the preferences of journal editors and readers [19]. Another limitation of this study is that our data come from a single source, namely, Journal Citation Reports, as opposed to others that consider Scopus, which is thought to have a wider coverage [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The temporal increase in the number of references per papers varies among different disciplines (Sánchez- Gil et al, 2018). Furthermore, Nicolaisen and Frandsen (2021) showed that "there is a drop in short reference lists and a corresponding increase in a bit longer and medium size reference lists. Long and very long reference lists remain much more stable in shares over time, and does therefore not contribute much to the observed growth."…”
Section: Temporal Trendsmentioning
confidence: 99%